Protective effect of tomato-oleoresin supplementation on oxidative injury recoveries cardiac function by improving β-adrenergic response in a diet-obesity induced model - Ferron, Artur Junio Togneri [UNESP]; Aldini, Giancarlo; Francisqueti-Ferron, Fabiane Valentini [UNESP]; De Almeida Silva, Carol Cristina Vágula [UNESP]; Bazan, Silmeia Garcia Zanati [UNESP]; Garcia, Jéssica Leite [UNESP]; De Campos, Dijon Henrique Salomé [UNESP]; Ghiraldeli, Luciana [UNESP]; Kitawara, Koody Andre Hassemi [UNESP]; Altomare, Alessandra; Corrêa, Camila Renata [UNESP]; Moreto, Fernando [UNESP]; et al. (MDPI, 2019)
The system redox imbalance is one of the pathways related to obesity-related cardiac dysfunction. Lycopene is considered one of the best antioxidants. The aim of this study was to test if the tomato-oleoresin would be able to recovery cardiac function by improving β-adrenergic response due its antioxidant effect. A total of 40 animals were randomly divided into two experimental groups to receive either the control diet (Control, n = 20) or a high sugar-fat diet (HSF, n = 20) for 20 weeks. Once cardiac dysfunction was detected by echocardiogram in the HSF group, animals were re- divided to begin the treatment with Tomato-oleoresin or vehicle, performing four groups: Control (n = 6); (Control + Ly, n = 6); HSF (n = 6) and (HSF + Ly, n = 6). Tomato oleoresin (10 mg lycopene/kg body weight (BW) per day) was given orally every morning for a 10-week period. The analysis included nutritional and plasma biochemical parameters, systolic blood pressure, oxidative parameters in plasma, heart, and cardiac analyses in vivo and in vitro. A comparison among the groups was performed by two-way analysis of variance (ANOVA). Results: The HSF diet was able to induce obesity, insulin-resistance, cardiac dysfunction, and oxidative damage. However, the tomato-oleoresin supplementation improved insulin-resistance, cardiac remodeling, and dysfunction by improving the β-adrenergic response. It is possible to conclude that tomato-oleoresin is able to reduce the oxidative damage by improving the system’s β-adrenergic response, thus recovering cardiac function.
Keywords: Cardiac dysfunction; High sugar-fat diet; Lycopene; Obesity; Tomato-oleoresin; β-adrenergic system